2016
DOI: 10.3389/fpsyt.2016.00160
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Dysfunction, Affective States, and Vulnerability to Nicotine Addiction: A Multifactorial Perspective

Abstract: Although smoking prevalence has declined in recent years, certain subpopulations continue to smoke at disproportionately high rates and show resistance to cessation treatments. Individuals showing cognitive and affective impairments, including emotional distress and deficits in attention, memory, and inhibitory control, particularly in the context of psychiatric conditions, such as attention-deficit hyperactivity disorder, schizophrenia, and mood disorders, are at higher risk for tobacco addiction. Nicotine ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 393 publications
(386 reference statements)
2
29
0
Order By: Relevance
“…The effects of nicotine on mood and cognition might be dependent on different factors such as neurobiological/genetic background of the subjects. These leading to the substantial heterogeneity in the underlying causes of cognitive impairments in passive-smokers (Besson and Forget, 2016;Hall et al, 2015). Also the causal relationships may be due to the genetic relationships to the parents, not due to their smoking.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of nicotine on mood and cognition might be dependent on different factors such as neurobiological/genetic background of the subjects. These leading to the substantial heterogeneity in the underlying causes of cognitive impairments in passive-smokers (Besson and Forget, 2016;Hall et al, 2015). Also the causal relationships may be due to the genetic relationships to the parents, not due to their smoking.…”
Section: Discussionmentioning
confidence: 99%
“…It was suggested that downregulation of the dopaminergic system in the VTA, NAc and central nucleus of the amygdala (CeA), together with upregulation of corticotropin‐releasing factor (CRF) and norepinephrine systems in the CeA and VTA, underlie excessive nicotine intake, driven by negative reinforcement . For example, cocaine increases DA and 5‐HT release, but decreases in dopaminergic and serotonergic transmission were observed in the ventral striatum during cocaine withdrawal in rats .…”
Section: Clinical and Neurobiological Similarities Between Addiction mentioning
confidence: 99%
“…Because these psychiatric disorders are associated with various cognitive impairments, including deficits in attention, working memory, and response inhibition functions [ 17 , 18 ], the cognitive enhancing effects of nicotine may be especially important determinants of the initation and maintenance of smoking in this comorbid population. Growing evidence suggest that cognitive enhancing effects of nicotine may also contribute to the difficulty in quitting smoking, especially in individuals with psychiatric disorders [ 19 ].…”
Section: Introductionmentioning
confidence: 99%